In situ growth of ultra-smooth or super-rough thin films by suppression of vertical or horizontal growth of surface mounds. Issue 9 (4th February 2020) - Hu, Chaoquan; Cai, Jize; Li, Yuankai; Bi, Chaobin; Gu, Zhiqing; Zhu, Jiaqi; Zang, Jianfeng; Zheng, Weitao
Abstract : A new method and mechanism were explored for in situ growth of ultra-smooth/super-rough thin films with unique surface properties. Abstract : With the development of catalysis, self-cleaning, biomedicine, solid lubrication and precision contact technologies, there is increasing need for ultra-smooth and super-rough functional thin films. However, since the surface roughening mechanism of thin films remains vague, an effective method for in situ growth of ultra-smooth and super-rough films has not been proposed. In this paper, we find that the surface roughening rate ( ν R ) is proportional to the relative vertical-growth coefficient of the mounds ( δ ) through a series of experiments and simulations on hafnium nitride, hafnium oxide and silver films, which are three typical covalent bonding, ionic bonding, and metallic bonding materials, respectively. This suggests that the formation conditions of the ultra-smooth and super-rough surfaces are δ ≪ 1 and δ ≫ 1, respectively. Therefore, we propose an effective idea for in situ growth of ultra-smooth and super-rough films, which is to suppress the vertical and horizontal mound growth, respectively. By periodically introducing an amorphous layer ( e.g. a-CN) and doping the non-wetting inert metal ( e.g. Ag) during the deposition process, we effectively suppress the vertical and horizontal mound growth to prepare ultra-smooth and super-rough hafnium nitride films, respectively. The results show that the roughness range of the hafnium nitride films deposited by the new method is about 5 times larger than that reported in previous studies. Therefore, this study provides a complete understanding of the surface roughening mechanism of thin films and develops a general method for the in situ growth of ultra-smooth or super-rough films.